Facile preparation of ZnMn2O4 hollow microspheres as high-capacity anodes for lithium-ion batteries - Zhou, Liang (2013)
Uniform ZnMn2O4 hollow microspheres have been synthesized by a facile coprecipitation and annealing method. The resultant ZnMn2O4 hollow microspheres exhibit high specific discharge capacity, good rate capability, and excellent cycling stability. The improved electrochemical performance may be attributed to the beneficial features of reduced diffusion length for Li+ ions and enhanced structural integrity with sufficient void space for buffering the volume variation during the Li+ insertion/extraction.